Effects of limitation of number of alters and time frame in the burt name generator - Kogovšek, Tina (Metodološki zvezki, 2005)
Social networks can be operationalized as potential and actual sources of social support. Comparing cross-sectional data sets from various points in time allows us to compare overall characteristics of social support networks and their changes over time in the population. However, the measurement instruments should be identical or at least very similar. The Burt name generator (1984) for assessing discussion networks of Slovenians was applied in the 1987 and 2002 surveys. Data were collected on representative samples of adult residents of Slovenia. Owing to the complexity of the personal network questionnaire, the number of alters was limited to 5 in the 1987 survey, where as there was no upper limit in the 2002 survey. There was also a difference in question wording. In the paper these two surveys are compared with regard to network composition and structure. Special attention is given to the effects of limiting the number of alters, question wording and network size on statistical estimates of network composition and structure.
Keywords: Družboslovno raziskovanje; Social science research; Methodology; Metodologija; Networks; Omrežja; Measurement; Merjenje; družbena omrežja; analiza omrežij